Validasi Multimedia Pembelajaran Fisika Berbasis Inkuiri dengan Pendekatan Saintifik pada Materi Pelajaran Usaha, Energi dan Momentum untuk Meningkatkan Kemampuan Berpikir Kreatif - Silvia Irani; Hufri Hufri; Letmi Dwiridal (Universitas Negeri Padang, 2018)
Physics learning in accordance with the 2013 curriculum is needed by teachers who can improve the quality of learning, especially in terms of the ability of students to think creatively. One way to improve students' creative thinking skills in learning is to use inquiry-based physics learning multimedia. However, the fact that is found in the field that in learning physics has not fully utilized technology in learning and makes learning in school monotonous still because student just expect learning material from the teacher so that it is difficult to develop students' creative thinking skills. The aim of this reasearch is to design physics learning multimedia based on inquiry and know the value of validity for inquiry-based physics learning multimedia. The type of research used is research and development (R & D) and the object of research is inquiry-based physics learning multimedia. Based on data analysis obtained from 2 studies conducted. First, design physics learning multimedia based on inquiry with a scientific approach. Second, the average result of validation data analysis is 80.4 with valid criteria. So, it can be concluded that the inquiry-based physics learning multimedia with the scientific approach is declared valid and can be used in grade X physics learning in SMA.